2021
DOI: 10.3390/ijerph18095006
|View full text |Cite
|
Sign up to set email alerts
|

Older Adolescents Who Did or Did Not Experience COVID-19 Symptoms: Associations with Mental Health, Risk Perception and Social Connection

Abstract: After a decrease in detected cases in the summer, Europe faced the emergence of a second wave of coronavirus disease 19 (COVID-19). Few studies have investigated adolescents, who may constitute a target group with possible lower compliance to public health measures, particularly the social distancing measures. A total sample of 492 participants was included in the study, and the ages of the participants ranged from 18–24 years. According to the hypothesis of our study, the sample was divided into two groups: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…This aligns with PMT, HMB, and previous research associating threat appraisal with vaccine acceptance for both the COVID-19 and influenza vaccines, as well as other pandemic preventative behaviors [ 10 , 11 , 12 , 16 , 21 ]. This relationship is also consistent with models of adolescent risk taking, where adolescents tend to engage more in risky behaviors when perceived to be at lower risk of an outcome [ 31 , 32 , 45 ]. This study further builds on the literature by demonstrating a greater difference in risk perceptions between hesitant and non-hesitant participants than that of vaccinated and unvaccinated participants.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This aligns with PMT, HMB, and previous research associating threat appraisal with vaccine acceptance for both the COVID-19 and influenza vaccines, as well as other pandemic preventative behaviors [ 10 , 11 , 12 , 16 , 21 ]. This relationship is also consistent with models of adolescent risk taking, where adolescents tend to engage more in risky behaviors when perceived to be at lower risk of an outcome [ 31 , 32 , 45 ]. This study further builds on the literature by demonstrating a greater difference in risk perceptions between hesitant and non-hesitant participants than that of vaccinated and unvaccinated participants.…”
Section: Discussionsupporting
confidence: 84%
“…Given lagging vaccination rate in adolescents and increased variant transmissibility, understanding adolescent motivators is especially relevant [ 28 , 29 ]. Extant health behavior models have been applied to adolescents’ willingness to participate in other COVID-19 preventative behaviors, such as mask wearing and social distancing [ 30 , 31 , 32 ], yet there is a lack of research empirically investigating adolescents’ drivers of COVID-19 vaccine acceptance [ 14 , 27 ]. Among the relatively limited research on this age population, earlier studies often surveyed parents about their children and rarely directly queried adolescents to obtain their attitudes and perceptions [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This allowed only for virtual meetings and prohibited face-to-face meetings with peers, teachers, family, or friends. Several studies have found that lockdowns resulted in increased isolation and loneliness (e.g., Burrai et al, 2021 ). Loneliness during the COVID-19 lockdown has been associated with several negative mental health outcomes, such as depression and suicide, and has remained elevated despite the easing of lockdowns (Killgore et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…AYAs with self-perceived risk and desire to protect others were significantly associated with higher adherence to preventive measures [10] . Likewise, higher perceived self-efficacy to take preventive measures was associated with a greater perceived severity of the COVID-19 disease [11] . Factors associated with higher risk perception included greater disease knowledge, presence of chronic disease, and use of immunosuppressants [10] .…”
Section: Introductionmentioning
confidence: 91%